PEMETAAN MOBILITAS PENDUDUK DI KAWASAN PINGGIRAN KOTA BUKITTINGGI - Ramadhana, Yolla; Syarief, Azhari (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
The objective of this research is to observe the level of population mobility in the outskirts of Bukittinggi City and analyze the mobility patterns occurring in the region. The research employs a quantitative descriptive methodology, utilizing data collection techniques through field observations and interviews. For data mapping, spatial analysis is conducted using Geographic Information System (GIS) with overlay techniques. Findings from the study at four observation points indicate that the inflow of vehicles surpasses the outflow, with the highest vehicle influx recorded on Wednesdays, reaching 37,411 vehicles. This suggests a dependency of the outskirts on Bukittinggi City, particularly in economic, educational, health, and tourism activities. The observed mobility patterns are predominantly daily in nature. Thus, addressing mobility challenges involves enhancing the quality of access to Bukittinggi City and developing infrastructure in the outskirts to alleviate the burden on the city center.